2011
DOI: 10.4103/1596-3519.76592
|View full text |Cite
|
Sign up to set email alerts
|

Severe pentasomide Armillifer armillatus infestation complicated by hepatic encephalopathy

Abstract: Background: Diagnosis of Armillifer armillatus infestation is usually incidental, commonly via autopsy or radiography. Affected individual are usually asymptomatic. The case presented here, however, had severe thoracic and abdominal involvement with clinical manifestations. Aim: To report a case of heavy A. armillatus infestation in an adult female Nigerian rural dweller complicated by hepatic parenchyma damage. Setting: Case report from semi-urban southern Nigeria, using clinical records and imaging findings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…2 Most often, the liver, mesenteries, spleen, and lungs are affected, 2 and patients report fever, abdominal pain, vomiting, diarrhea, jaundice, and abdominal tenderness. 4 Severe and possibly lethal cases, such as massive infection of the liver, 13 mechanical ileus, 14 and other dissemination, 15 are very rare. In the case described here, the symptoms reported were most likely caused by the pancreatic malignancy, and the pentastome infection was an incidental finding.…”
Section: Discussionmentioning
confidence: 99%
“…2 Most often, the liver, mesenteries, spleen, and lungs are affected, 2 and patients report fever, abdominal pain, vomiting, diarrhea, jaundice, and abdominal tenderness. 4 Severe and possibly lethal cases, such as massive infection of the liver, 13 mechanical ileus, 14 and other dissemination, 15 are very rare. In the case described here, the symptoms reported were most likely caused by the pancreatic malignancy, and the pentastome infection was an incidental finding.…”
Section: Discussionmentioning
confidence: 99%
“…Infection is usually asymptomatic [1]; however, symptomatic [3], severe [4] and even fatal [5] Armillifer infections have also been reported. Risk factors of this infection include the handling of snakes or snake products, consumption of undercooked snake meat, and possibly snake farming and snake totemism [1], [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…He however admitted consumption of Alligator. The fact that he is from South-south Nigeria where he may have had several encounter with water contaminated with the parasite coupled with the fact that other reptiles like alligator could be infective may be the reason for his disease [ 16 ]. The first and third patients had no features specific for armillifer Armillatus infestation while the second case presented with non-specific dry cough on two occasions at two month interval.…”
Section: Discussionmentioning
confidence: 99%
“…Both episodes of cough were treated conservatively and he did well following treatment. The cough may not be related to the infestation, but previous publications by other authors revealed some cases of pneumonitis that occurred as a result of Armillifer armillatus infestations [ 16 ]. In patients with severe infestation, there could be associated pericarditis, pleuritis, acute abdominal conditions such as intestinal obstruction and even viscus perforation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%